A new subspecies of Sedum confertiflorum Boiss. (Crassulaceae, Sedeae) from Evvia Island (W Aegean, Greece) - Trigas, Panayiotis; Polymenakos, Kostas (Phytotaxa, 2026)
A new subspecies, Sedum confertiflorum subsp. euboicum, is described from Mt. Ochi in southern Evvia Island, Greece. Morphological comparisons with typical S. confertiflorum, known from Anatolia, Lesvos Island, northeastern Greece, and South Bulgaria, revealed consistent differences in size, inflorescence structure, and flower morphology. These differences, though not sufficient for species-level distinction, justify recognition at the subspecific level. The new subspecies is currently known from a single high-altitude locality (1,170 m) on a small rocky plateau and is estimated to number fewer than one thousand individuals. Its discovery highlights the biogeographic singularity of Evvia, where Balkan, Aegean, and Southwest Asiatic floristic elements co-occur.